DEVELOPMENT OF ORGANIZATIONAL MANAGEMENT IN IMPROVING BUSINESS SUSTAINABILITY IN STRUCTURAL KEBANAN (WINNER OF THE STUDENT DIGITAL ENTREPRENEURSHIP INNOVATION CHAMPIONSHIP) - Hadi, Syamsul; Kirana, Kusuma Candra; Cahyaning, Enggar Kartika; Grace, Flora; Rokhman, Nur; Wildan, Muh Khaerul; Salma, Syarifah; Choirunnisa, Ayu Rizka; Iswantoro, Ibnu Yanuar; Andleeb, Naima (EMPOWERING HUMANITY, 2023)
Background- KEBANAN is one of the on demand service platforms created by students at Bachelorwiyata Tamansiswa University as a result of the Student Digital Entrepreneurship Innovation Program championship of the Indonesian Ministry of Education and Culture. KEBANAN is based on a mobile application that can provide a solution to banan when experiencing problems on the road with the tagline "Kebanan, so you are calmer when a tire leaks on the road". Structural Problems KEBANAN is a team of students from the UST (graduatewiyata Tamansiswa University) management study program who are currently taking their 6th semester including the Director, Production and Product Development Team, as well as the market and distribution development Team. Obligations at the end of semesters 6-7 are very high because you are required to do internships, real work studies, and thesis writing which require extra focus in terms of time, energy, and thought, so that the continuity of KEBANAN will be disrupted because the entire structure will focus on graduating on time as a main priority. If problems like this are not immediately addressed and educated, it will be worrying that the business life cycle will be shortened, and if that happens it is very unfortunate because KEBANAN has a strategic role in providing solutions for road users when there is a ban on the road. The aim of developing organizational management is to increase the sustainability of the KEBANAN startup business as the best solution. The solution to overcome this problem is in 7 ways, namely: How the team spends time, How to make a daily activity schedule, How to prioritize time wisely, How to group similar tasks, Set time limits when working on tasks, Learn to say no and eliminate distractions. After discussion, the entire KEBANAN team realized that they needed to change and made a commitment to become motivated again, starting with proper time management.